FRUSTRATION AND HOPE: A REVIEW OF THE RESPONSE UNDERTAKEN IN NATIONAL EDUCATION PROGRAMMES TO LOWER-THAN-EXPECTED RATES OF FOREIGN LANGUAGE ACQUISITION (Investigación y Desarrollo, 2020)
This review and discussion focused on surveys and reports regarding the rate of foreign language acquisition and attainment within national compulsory education systems, academic analyses of the results obtained, and national programmes and initiatives designed to address the shortcomings revealed in them.  The proposed reasons for lower-than-expected acquisition and attainment in foreign language learning within countries including the European Union, Colombia, Vietnam and Ecuador were reviewed in detail. These reasons, and the measures undertaken as a result to remedy these flaws, were evaluated through a comparison with recent academic research relating to these factors, and through com- parison between the different experiences revealed in the surveys and reports.  These comparisons found that some of the measures undertaken were fit for purpose and were likely to yield some improvements in acquisition rate, although to a lesser extent than those projected by some of the national programmes, while identifying some aspects which have been overlooked. The conclusion highlighted in which aspects of the teaching and learning of foreign languages requires greater focus is needed in order to effect the desired changes.